The changing economic order in China: Trends and limitations - Armin Bohnet (Intereconomics, 1988)
Far-reaching changes in the People's Republic of China's economic and social policy have been decided and carried out since 1978. The following article analyses a number of selected aspects of the economic order to illustrate the direction the reforms are taking and the limitations to which they are subject.
Keywords: 330; PR China